2004
DOI: 10.1103/physreve.69.055601
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of simultaneously large and opposite generalized Goos-Hänchen shifts for TE and TM light beams in an asymmetric double-prism configuration

Abstract: It is predicted that large and opposite generalized Goos-Hänchen (GGH) shifts may occur simultaneously for TE and TM light beams upon reflection from an asymmetric double-prism configuration when the angle of incidence is below but near the critical angle for total reflection, which may lead to interesting applications in optical devices and integrated optics. Numerical simulations show that the magnitude of the GGH shift can be of the order of beam's width.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…(8), the reflected field in Eq. (6) can be found in a similar way. Here, in addition, we have to expand the reflection coefficient in Eq.…”
Section: B Reflected Beam Fieldmentioning
confidence: 57%
See 1 more Smart Citation
“…(8), the reflected field in Eq. (6) can be found in a similar way. Here, in addition, we have to expand the reflection coefficient in Eq.…”
Section: B Reflected Beam Fieldmentioning
confidence: 57%
“…(1), the GH shift even for (partial) reflection from an absorbing medium. The result, although attracting some attention, [5][6][7][8] needs substantiation and generalization, especially in view of the question of an undistorted beam because of a small and angle-dependent reflection coefficient at and around Brewster's dip. The present paper is intended exactly to address this and other related questions.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations have shown that the GH shift of the transmitted electrons can be enhanced by transmission resonances in graphene or other nanostructures. 24,[26][27][28] In this study, we propose an effective way to realize an electron spin beam splitter by using the GH effect in graphene. We investigated the spatial separation of the spin-up and spin-down electron beams through a structure (shown in Fig.…”
mentioning
confidence: 99%
“…The peaks of the theoretical shifts are about −4.54λ for the perpendicular field and 24.25λ ( 19.66λ ) for dip I (dip II) of the parallel field. It is noted that the discrepancy between theoretical and numerical results is due to the distortion of the reflected beam, especially when the waist of the incident beam is narrow [36]. Further numerical simulation shows that the wider the incident beam is, the smaller the discrepancy is.…”
Section: Resultsmentioning
confidence: 90%